NUMERICAL MODELING OF PRESSURE DROP IN SUBSURFACE SAFETY VALVES - JAMALIATUL MUNAWWARAH MOHD ALISJABANA, JAMALIATUL (Universiti Teknologi Petronas, 2012)
This report will present on the research done for the project entitle “Numerical Modeling of Pressure Drop in Subsurface Safety Valves.” The project objective is to develop a numerical model that could determine the pressure changes across the Subsurface Safety Valve (SSSV) by using Wolfram Mathematica software. By having this numerical model, we are also able to run sensitivities on the parameters that could affect the pressure drop. It is hope by having this project, a dynamic control over the SSSV can be achieved as a function of fluid flow parameters. In this report, literature review is done on the introduction to SSSV and how it is operated, the flow behavior and also on the concept of pressure drop in SSSV. Project methodology and activities have been designed and the milestone for this project has been planned. The mathematical procedures and the program code flow chart are also included in the report. This report also presents the single and two phase flow computer code that has been completed and also the results and analysis of the sensitivities run on the parameters that could affect the pressure drop across the SSSV. In conclusion, the project has been successfully completed and it is hope that this project is able to be applied in the industry.